The complete chloroplast genome sequence of Rosa minutifolia - Zhao, Xia (Mitochondrial DNA B Resour, 2020)
Here we report the chloroplast genome sequence of Rosa minutifolia. This rose grows in warm climates, it has been reported as an endangered species. The complete chloroplast genome size was 157,396 bp, and exhibited a quadripartite structure with dual inverted repeats (IRs) regions (26,041 bp), a small single-copy (SSC) region (18,775 bp), and a large single-copy (LSC) region (86,539 bp). The genome contained a total of 137 genes including 90 protein-coding genes, 39 tRNA genes, and 8 rRNA genes. Phylogenetic analysis revealed that R. minutifolia is closely related to R. rugosa and R. hybrid cultivar Augusta.